Hospitalization is less in malnourished patients given intradialytic oral nutritional supplements - Eduardo Lacson Jr; Weiling Wang; Barbara Zebrowski; Rebecca Wingard; Raymond Hakim (The Korean Society of Nephrology, 2012)
Use of intradialytic oral nutritional supplements (ONS) improve nutritional biomarkers but an association with hospitalization risk is unexplored. We evaluated hospitalization events from all causes (HOS), comparing patients with serum albumin ≤3.5 g/dL who received monitored ONS (at no patient cost) during chronic outpatient hemodialysis (HD) as part of a standardized national program in Fresenius Medical Care, North America facilities, with eligible patients who did not receive ONS (controls). Study enrolment covered Q4‐2009 and follow‐up was until 12/31/10. Patients who received ONS outside of the program or started during 2010 were excluded. Two protein bars and two liquid formulations of ONS options were offered - - which were available until albumin was ≥ 4.0 g/dL. Overall, HOS was lower in the ONS group (N= 7,264) at 2.5 vs. 2.7 episodes/pt‐year for controls (N= 13,853), p<0.001. The unadjusted time to 1st HOS hazard ratio for ONS was 0.92 (0.88, 0.95) and after adjustment for baseline case‐mix, HOS 30‐days prior to study entry, and 5 HD quality indicators was 0.93 (0.90, 0.96). Although limited by the observational design, these results indicate lower HOS associated with ONS use in malnourished chronic HD patients with albumin ≤3.5 g/dL.